VISUAL POLLUTION CAN HAVE A DEEP DEGRADING EFFECT ON URBAN AND SUBURBAN COMMUNITY: A STUDY IN FEW PLACES OF BENGAL, INDIA, WITH SPECIAL REFERENCE TO UNORGANIZED BILLBOARDS - Jana, Milan Kumar; De, Tanaya (European Scientific Journal, ESJ, 2015)
When we look around, our first impression of any environment is the visual environment. This is a conglomeration of some constructed forms intermingled with the natural surroundings. In recent times, the term pollution signifies an inclusion of those affecting in a subtle way such as visual pollution. This kind of pollution affects the overall well-being and thus the quality of life of a community, reduces aesthetic appeal, economic health and civic-sense. This may incite a psychological aversion and thus affect mental and physical health of neighbouring residents. Visual pollution, thus, may be defined as the whole of irregular formations, represents unorganized dumping of litters, billboards, cables, wires, worn-out buildings, heaped construction materials, graffiti etc. that affects a person’s ability to enjoy a view or vista. This work aims at drawing attention to the hazardous and penetrating effects of the visual pollutants with special reference to unorganized billboards and to make realize that the visual environment is no less significant a part of the fabric of communities as clean water or air and animal habitat. Different places of Kolkata (South and North) and of Barrackpore and Barasat of 24-Paraganas (N) district, West-Bengal, India, were explored for abundance of visual pollutants, especially the ubiquitous billboards appearing like ghosts all around the cities and townships. Possibilities of some associated hazards were observed too. A comparison was done between areas that were visually pleasant and unpleasant. The psyche of people was followed and their innate instinct regarding visual quality of an environment was asked. The social civility and the behavior of people around solid waste were observed. It was found that in the cityscape visual pollutants were omnipresent, billboards misarranged, torn, with bare skeletons looming large in almost all nook and corner. They were found in residential areas as well as in front of social institutions like school, hospital, church, and temple. This unsightly presence creates deep displeasure, aesthetic-appeal, thus civic sense, aesthetic appeal of the community declines and hence psychological health is bound to be affected. This is compounded with indispensible apprehension of general health hazards of different dimensions including diseases and problems like asthma, diarrohoea etc around solid waste, cause infection to animals hovering around it, driver’s problem, missing of traffic signal by dazzling billboards, health problems caused by magnetic-field around cables, may create a short-circuit problem which may be extremely dangerous on water-logged roads. Some birds get electrocuted often due to exposed cables. The most vital aspect is, since this type of pollution is an aesthetic issue and have not been paid heed to earlier, hence the impact of its effect on society as a whole have remained largely undocumented. There is no denial of the fact that the sight of a beautiful natural environment stimulates human beings, soothes their soul. Conversely, the ugly sight triggers irritability. Children growing up in its vicinity get used to it losing their ability to understand the need for correcting it. This results in character-changing effects, the unique identity of the community is homogenized and entire life-style is deteriorated.